POLA KEJADIAN TB PARU: STUDI TENTANG HUBUNGAN STATUS EKONOMI DAN KONDISI FISIK RUMAH - Muthmainnah, Muthmainnah; Yuliza, Emi; Rahakbauw, Grenny Zovianny; Mariani, Andi; Assagaff, Farha (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Based on the results of the initial survey, it is known that the highest number of Tb cases in Riau Province occurred in Pekanbaru City with 3361 cases. One of the Puskesmas working areas with the highest Tb cases is the Umbansari Puskesmas working area. The results of observations generally the community has a job with an income that is still below the minimum wage, meaning that the economic status in the community specifically suffering from Pulmonary TB is more prevalent than the economic status above the minimum wage standard. The purpose of the study was to determine the relationship between economic status and physical condition of the house with the incidence of Tb. The type of research is quantitative with a cross sectional approach. The research was conducted at the Umbansari Health Center work area in 2023. The sample amounted to 78 people. The results showed that there was a relationship between economic status (p value 0.000) and physical condition of the house (p value 0.011) with the incidence of Tb. It is suggested that the Puskesmas is expected to use the results of this study to improve contact investigation to reduce the incidence of TB and break the chain of transmission, especially related to contact history.Keywords: Economy, Physical House Condition, Tuberculosis